Diagnostic utility of fine‐needle aspiration cytology in syphilitic lymphadenitis: A case report. Issue 6 (14th March 2023) - Yorita, Kenji; Ohara, Masahiko; Tahara, Kazuhiko; Fujioka, Ai; Miyazaki, Katsushi; Takeda, Takashi; Mizuno, Keiko; Yasuoka, Kaori; Wada, Yukari; Tsutsui, Hiroyuki
Abstract: Syphilis is a sexually transmitted infection that causes serious health problems without treatment. Detection of syphilis is necessary to stop the spread of the infection. Cytological screeners and pathologists may experience fine‐needle aspiration cytology (FNAC) for syphilitic lymphadenitis; however, its characteristic cytological features are rarely reported. We present FNAC cytological features of syphilitic lymphadenitis in a case of a 21‐year‐old man. He presented with a sore throat and painful neck lymphadenopathy. His swollen and painful neck persisted even with antibiotic treatment. Necrotizing lymphadenitis and lymphoma were clinically suspected. FNAC was taken from the swollen lymph node. Cytologic findings of the specimen showed various inflammatory cells with small‐sized vessels arranged in a branching/arborizing fashion. The vessels were surrounded by inflammatory cells, including plasma cells, neutrophils, and macrophages. Perivascular plasma cell cuffing was focally seen along with inconspicuous granulomas. Neutrophils appeared to involve the vascular wall. The cytological findings suggested syphilitic lymphadenitis, and clinical findings and serological tests confirmed primary syphilis with concomitant human immunodeficiency virus infection. Branching/arborizing vessels associated with many plasma cells, vascular involvement of neutrophils, and granulomas may suggest syphilitic infection if the specimen is obtained via FNAC. (189 words).